Managing Insurance Company Financial Statements to Meet Regulatory and Tax Reporting Goals* - GAVER, JENNIFER J.; PATERSON, JEFFREY S. (Contemporary Accounting Research, 1999)
Abstract This study investigates the extent to which property‐casualty insurers select levels of loss reserves, net capital gains, and net stock transactions to meet solvency and tax reporting goals. Insurer solvency is reflected in financial measures known as IRIS (Insurance Regulatory Information System) ratios. IRIS ratios are generally enhanced by underestimating loss reserves, accelerating the realization of capital gains, postponing the realization of capital losses, issuing stock, and cutting dividends. Taxable income is reduced by reporting higher reserves and lower net capital gains on investments. We use simultaneous equations to model the three discretionary choices individually, while controlling for potential tradeoffs among the decisions. During the sample period of the study (1990‐95), there is a shift in the regulatory environment that we argue tends to reduce incentives to meet IRIS goals. Specifically, risk‐based capital (RBC) requirements were adopted in 1994. Although IRIS ratios continued to be used for solvency screening, their effect is expected to be diluted in the post‐RBC period. Our results provide qualified support for this claim. Evidence of the phenomenon is stronger when the choice variables are net capital gains and stock transactions, and weaker when loss reserves are considered. Two of the three discretionary choices affect taxable income: loss reserves and capital gains. We find that tax incentives are significantly associated with the loss reserve estimate throughout the sample period. In contrast, our results are only weakly consistent with the view that capital gains are timed to achieve tax relief.